Low-power cmos cross-coupled differential-drive rectifier for ambient radio frequency energy harvesting systems / Gabriel Chong Sing Leung - Gabriel Chong , Sing Leung (2020)
Wireless Sensor Node (WSN) for the Internet of Things (IoT) and Internet of Everything (IoE) will require harvesting low-power ambient Radio Frequency (RF) energy to achieve self-power capabilities, alleviating the need of batteries. The research title of “Low-Power CMOS Cross-Coupled Differential-Drive Rectifier for Ambient Radio Frequency Energy Harvesting Systems” relates to the design of integrated circuit (IC) rectifiers for low-power ambient RF energy harvesting (RFEH) in complementary-metal-oxide-semiconductor (CMOS) technology. The adoption of CMOS for the rectifier designs is to achieve small physical form factor, low-cost, and system-on-chip (SoC) integration. The rectifier is the main circuit in an ambient RFEH system to convert the scavenged RF power in alternating current (AC) into usable direct current (DC) for powering WSNs. The Cross-Coupled Differential-Drive (CCDD) rectifier is the selected choice in this thesis due to its high peak power conversion efficiency (PCE) and low sensitivity. However, the dynamic range (DR) efficiency of this topology restricts high-PCE-range performance due to the inherent low-power of ambient RF energy. The rectifier’s ability to convert ambient RF power into usable DC level present a bottleneck in achieving high PCE across input RF power range.